Comics as a multimodal resource and students' willingness to communicate in Russian. Issue 2 (4th March 2022) - Calafato, Raees; Gudim, Freda
ABSTRACT: The multimodal nature of daily interactions in the twenty-first century has led to growing calls for the inclusion of multimodal content like comics in foreign language classrooms. Such content, as opposed to traditional language textbooks, can boost learners' self-confidence and more effectively develop their multimodal competence, including their willingness to use foreign languages via diverse media. This article reports on an exploratory study involving a teacher of Russian as a foreign language (RFL) and her students that investigated how the use of comics as a pedagogical resource affected the students' willingness to communicate (WTC) in Russian, the teacher's level of engagement with her students, and her professional development. The study drew on interviews, classroom observations, and samples of students' written production over two semesters. The study's findings revealed that the use of comics boosted the students' WTC in Russian multimodally, as well as their desire to read in the other languages they knew. The students exhibited a greater willingness to speak Russian during lessons, interact with others in Russian via social media networks, produce art that incorporated Russian, and engage in performative behavior using Russian in the classroom and beyond. GRAPHICAL ABSTRACT: uf0001